Job vacancies in Colombia: 1976-2012 - Andrés Álvarez; Marc Hofstetter (IZA Journal of Labor & Development, 2014)
Based on the counting of Help-wanted advertisements in print newspapers, we build national vacancy indexes and vacancy rates for Colombia for the period 1976 - 2012. The result is the first dataset capturing the evolution of vacancies for Colombia and the first one covering such a long period for any developing country. We publish the series in the Additional file 1; an online version is also available at http://economia. uniandes.edu.co/vacantescolombia. We explain how we built the series and tackle the most important questions concerning some issues about the representativeness of the resulting vacancy rate. These series will allow tackling many questions related to the functioning of the labor markets in emerging economies, where such datasets were not available. We relate the vacancy rate with the Colombian business cycle and estimate a Beveridge curve. We find that the vacancy rate is procyclical while the latter relationship presents the expected downward slope between vacancies and unemployment with a structural change-an outward shift-around 1986.
Keywords: E24; E32; J63; J64; 330; Vacancies; Help-wanted index; Unemployment; Beveridge curve; Labor market; Colombia